A Comparison of Hot Deformation Behavior of High‐Cr White Cast Iron and High‐Cr White Cast Iron/Low Carbon Steel Laminate. Issue 6 (10th September 2015) - Xu, Jianzhong; Gao, Xingjian; Jiang, Zhengyi; Wei, Dongbin
Abstract : In order to study the plastic deformation characteristics of the brittle high‐Cr white cast iron in upsetting process, and find out the mechanism for improving the formability of the cast iron within the laminated composite, the hot forging process of monolithic high‐Cr white cast iron and high‐Cr white cast iron/low carbon steel laminate is simulated by means of hot compression tests using Gleeble 3500 thermo mechanical simulator and professional plastic forming software DEFORM‐3D. The results reveal that during hot compression process, the monolithic cast iron suffered severe barreling and cracking, whereas the cast iron layer within the laminate underwent large plastic deformation with barreling‐free and crack‐free. Such a significant improvement can be attributed to the simultaneous deformation of the cast iron together with the low carbon steel claddings, which is beneficial to relieving the stress in the cast iron and changing its deformation mode. Under the triaxial compressive stress state, the brittle high‐Cr white cast iron within the laminate can flow like a ductile material at high temperatures and low strain rates. Abstract : Hot deformation behavior between the brittle high‐Cr white cast iron and high‐Cr white cast iron/low carbon steel laminate in upsetting process is compared. During deformation process, the monolithic cast iron suffers severe barreling and cracking, whereas the cast iron layer within the laminate undergoes large plastic deformation with barreling‐free and crack‐free. The mechanism for this improvement is discussed.